Usaha Telur Asin Aneka Rasa Lombok - I Made Suardana; Rusli Amrul; Ni Nyoman Yuliati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
There are two groups in this devotion activity namely ODGJ 1 which located in the  Gomong Mataram and ODGJ 2 in Dasan Agung Mataram. The target group in this activity is the people with mental disorder group that is group of people with mental disorder but has been declared recovered from mental disorder. This mental disorder group includes the productive age group and if not empowered will experience economic downturn which resulted  the poverty rate of this group will increase. This devotion started activities held on June 3, 2017 - 30 September 2017.The main problems of the mental disorder group are poor management and financial management skills, the skill of packing and labeling of the product has not been understood, and the cooperation network with others is not yet known. This condition causes the target group's efforts to be poorly developed. The results of this activity can be seen from the implementation after the training is done. Processing of the product up to the packaging and labeling done well by the mental disorder group. The recording of financial transactions is done well on a special financial book. The business license is still under way to make salted egg products more widely known and widely known by many parties.